Evaluation of the safety, tolerability, and pharmacokinetics of RO7049389 in healthy Chinese volunteers - Xiaojie Wu; Sheng Feng; Jing Zhang; Wenhong Zhang; Yuchen Zhang; Mingfen Zhu; Miriam Triyatni; Na Zhao; Qingyan Bo; Yuyan Jin (Clinical and Translational Science, 2022)
Abstract The objectives of this phase I study are to assess the safety, tolerability, and pharmacokinetics (PKs) of RO7049389 in healthy Chinese volunteers (HVs) and evaluate potential ethnic differences in the safety and PKs using data from this study and the first‐in‐human study (in which most of the HVs were non‐Asian). HVs randomly received a single dose of 200–600 mg of RO7049389 or a placebo in a single ascending dose (n = 28) or multiple doses of 200–400 mg of RO7049389 or a placebo in multiple ascending doses (n = 24). Safety and tolerability were monitored throughout the study. Serial blood samples were collected for PK analysis. RO7049389 was safe and well‐tolerated in the HVs. The time to maximum concentration ranged from 1.5 to 3.0 h, and terminal half‐life ranged from 3.66 to 14.6 h. A single dose of 200–600 mg and multiple doses of 200–400 mg exhibited nonlinear PKs. In general, the safety profiles were comparable between non‐Asian and Asian HVs, but the plasma exposure of RO7049389 in Chinese HVs was higher than that in non‐Asian HVs. The data generated from this study will provide guidance for future clinical studies on RO7049389 in Chinese/Asian patients with hepatitis B virus.